Mapping the Sensitivity of the Amundsen Sea Embayment to Changes in External Forcings Using Automatic Differentiation. Issue 23 (6th December 2021) - Morlighem, Mathieu; Goldberg, Daniel; Dias dos Santos, Thiago; Lee, Jane; Sagebaum, Max
Abstract: Thwaites and Pine Island Glaciers as well as other ice streams in West Antarctica have been changing dramatically over the past decades. Although changes in ocean conditions are likely the primary driver of these changes, it remains unclear where other processes could cause more mass loss. By employing Automatic Differentiation and two independent ice‐sheet models, we construct maps of the sensitivity of the volume above floatation to changes in ocean‐induced melt rates, ice rigidity, basal friction, and surface mass balance. We find that changes in basal melt close to the grounding lines and along shear margins have a larger impact on the glaciers' final volume. The glaciers are sensitive to changes in basal friction on regions close to the grounding lines, while changes in ice rigidity has a larger impact along the shear margins of Pine Island. The sensitivity to surface mass balance is uniform over grounded ice. Plain Language Summary: The Amundsen Sea Embayment is the region of Antarctica that is changing the fastest. Pine Island and Thwaites Glaciers have been thinning and accelerating over the past three decades and it is not clear whether they are going to continue to do so over the coming years. Here, we use two models of ice‐sheet flow and employ a new tool that shows what physical process is the most critical, and where, if we are interested in the future contribution to sea‐level rise of this sector of Antarctica. We find that the basal friction close to the zone where the ice starts to float exerts a very strong control on the mass balance. We also find that the connection between grounded ice and pinning points under the ice shelf is key to keep the system stable. Increasing basal melting or weakening the ice in this sector would lead to significant acceleration and further mass loss. Key Points: Future ice discharge is sensitive to basal conditions within 60 km of the grounding zone Pine Island Glacier's projected mass balance is most sensitive to the strength of its shear margins The integrity of Thwaites' ice shelf connecting to the Eastern Ice Rise is critical